(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
The article is devoted to the peculiarities of determination of seismic loads on steel silos with a flat bottom according to newly introduced DBN B.2.6-221:2021, harmonized with the global system of European codification Eurocode. The main focus is on the general methods of specifying seismic action and the principles of schematizing seismic action for analysis silos. The parameters of the acceleration spectra of the horizontal and vertical components of seismic load and their influence on formation of silos reaction in these directions are analyzed. The recommendations are given for accurate evaluations the inertia-stiff characteristics of silos with a flat bottom in height based on the analysis of their design features and physical and mechanical characteristics of the particulate material.